ELECTIONS AND ELECTORAL SYSTEMS - Moon, Woojin (The Oxford Handbook of South Korean Politics, 2021)
This chapter explains how the electoral system in South Korea has formed into a two-party-dominated system and identifies the elements that prevent a third party from winning seat shares proportional to its vote share. The chapter discusses the features that characterize political parties’ campaign strategies and the voting behaviour of South Korean citizens. Candidates pursue personal votes by focusing on negative campaigning and advertising their valences. This chapter also identifies two major position issues over which political parties compete and citizens make voting decisions. Although redistributive issues have recently become more salient, electoral competition has long revolved around inter-Korean issues. Citizens’ socio-economic statuses only have a meagre effect on their partisan support. Instead, citizens’ political attitudes have been formed differently across generations, as they have been exposed to different levels of anti-communism. Finally, the chapter explains the variation in regional voting in terms of party system polarization. As the ideological difference between parties has decreased, regional voting has intensified.
Keywords: anti-communism; campaign strategies; electoral rules; party system polarization; regional voting; two-party-dominating system; valences versus policies